The Potential of Combination Probiotics to Improve Feed Intake and Final Body Weight in Broiler Chickens Infected with Eimeria tenella - Dwinanda Budiwardani; Widya Paramita Lokapirnasari; Emy Koestanti Sabdoningrum; Sunaryo Hadi Warsito; Epy Muhammad Luqman; Agus Sunarso (Journal of Basic Medical Veterinary, 2026)
Broiler production in Indonesia continues to increase in line with the rising demand for animal protein. However, coccidiosis caused by Eimeria tenella remains a major constraint, as it disrupts nutrient absorption and negatively affects growth performance, particularly feed intake and body weight. The use of ionophore anticoccidials, such as monensin, is effective; however, concerns regarding antimicrobial resistance and drug residues highlight the need for alternative strategies, including combination probiotics. This study aimed to evaluate the potential effect of combination probiotics administered through drinking water on production performance, including feed intake (FI) and final body weight (FBW), in broiler chickens infected with E. tenella. A total of broiler chickens were assigned to five treatment groups: uninfected control (P0−), infected control (P0+), monensin treatment (P1), probiotic treatment (P2), and combined probiotic plus monensin treatment (P3). Data were analyzed using analysis of variance (ANOVA), followed by a post hoc test at a significance level of p < 0.05. The results showed that feed intake did not differ significantly among treatments (p > 0.05). However, final body weight was significantly affected (p < 0.05), with the highest value observed in the combination treatment group (P3), reaching 3192 g. The combination of Lacticaseibacillus paracasei and Pediococcus pentosaceus improved final body weight without affecting feed intake in broiler chickens infected with E. tenella. These findings indicate the potential of combination probiotics as a supportive strategy for maintaining growth performance under coccidial infection conditions.